2019
DOI: 10.29333/ejgm/110171
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between air pollution and outpatient visits for nonspecific conjunctivitis in Taiwan

Abstract: Background: As a directly exposed part of the human body, the eyes are susceptible to external stimulations of air pollution. The ill effects of air pollution on human eyes are mostly irritation and inflammation, with conjunctivitis being a significant problem. Method: This study investigates the impact of air pollution on nonspecific conjunctivitis based on the data from ophthalmologic outpatient visits. The research focuses on the significance of air pollution's impact on ocular health. Data for ophthalmolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…43 Higher levels of O 3 were also associated with the risk of developing nonspecific conjunctivitis (t-value = 2.292; p = 0.025) in a case-crossover study. 39 A time-stratified casecrossover study from China reached a similar conclusion. 36 Multivariate conditional logistic regression analyses showed that a 10 ppb increase in O 3 was positively associated with conjunctivitis (OR = 1.04; 95% CI: 1.03-1.04).…”
Section: Ozonementioning
confidence: 70%
See 4 more Smart Citations
“…43 Higher levels of O 3 were also associated with the risk of developing nonspecific conjunctivitis (t-value = 2.292; p = 0.025) in a case-crossover study. 39 A time-stratified casecrossover study from China reached a similar conclusion. 36 Multivariate conditional logistic regression analyses showed that a 10 ppb increase in O 3 was positively associated with conjunctivitis (OR = 1.04; 95% CI: 1.03-1.04).…”
Section: Ozonementioning
confidence: 70%
“…A cohort study identified that there was a positive association between higher levels of O 3 and allergic conjunctivitis (OR = 2.09; 95% CI: 0.49–3.69) 43 . Higher levels of O 3 were also associated with the risk of developing nonspecific conjunctivitis ( t ‐value = 2.292; p = 0.025) in a case‐crossover study 39 . A time‐stratified case‐crossover study from China reached a similar conclusion 36 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations